A solução consensual dos conflitos no contexto da lei de improbidade administrativa (Lei nº 8.429/1992): análise do ordenamento jurídico antes e depois da lei anticrime (Lei nº 13.964/2019) - Carvalho, Walmea Elyze (2020)
The present thesis intends to analyze the consensual solution of conflicts in the context of the Administrative Improbity’s Law, notably examining the normative statement contained in art. 17, §1o, of Law n. 8.429/92, from two perspectives: before and after the Anti-Crime Act (Law n. 13.964, published in December 24, 2019). After compare the legal system in these two legislative moments and highlight what changes the new law brought with the normative provision of the “civil non-prosecution agreement”, will be analyze its limits and contours – thinking about its future ratification by the Judiciary -, in particular, determining the minimum conditions that must be stipulated by dealers in order to preserve the principle of the supremacy of the public interest and the principle of the prohibition of deficient protection. In this regard, will be started the debate about the negotiating institute brought by the new legislation, de lege ferenda, in order to elaborate a theoretical framework to guide the performance of the dealers and contribute to elaborate a complementary legislative activity, without any pretension exhausting the topic and/or providing definitive answers to the various questions that accompany the recent Anti-Crime Law. In short, the central object of this thesis, inserted in the research line "Consensual Civil Procedure", is recognize the expansion of consensual justice for conflicts involving administrative improbity and, in this context, to encourage the academic debate on the subject, aiming at systematizing the agreement, in practical terms